Prostatic Adenosquamous Carcinoma Metastasizing to Testis. (2006) - Baydar, Dilek Ertoy; Kosemehmetoglu, Kemal; Akdogan, Bulent; Ozen, Haluk
Abstract : Adenosquamous carcinoma of the prostate is an unusual tumor with poor prognosis. Most arise after hormonal or radiotherapy of conventional prostatic adenocarcinoma. Sarcomatous transformation in them has been reported in only a few cases. Here, we present a unique case of "de novo prostatic adenosquamous carcinoma with focal sarcomatoid areas" that showed testicular metastasis, detected after scrotal orchiectomy.